Codex alimentarius commission: Procedural manual; Vol.11 - FAO (FAO, 2000)
The book divided into three sections: Section I sets out the Commission's basic Rules of Procedur and the other internal procedures necessary to achieve the commission's objectives; Section II is devoted to guidelines for the efficient operation of Codex Committees; Section II lists the Commission's susidiary bodies with their Terms of Reference. It also gives the Membership of the Commission together with the addresses of Codex Contact Points.